A Comparative Analysis of Radiographic Intervertebral Disc Height Following Full-Endoscopic Lumbar Discectomy: Interlaminar versus Transforaminal Approach - Pluemvitayaporn, Tinnakorn; Vikan, Supree; Pruttikul, Pritsanai; Surapuchong, Suttinont; Kittithamvongs, Piyabuth; Ratanakoosakul, Warot; Tiracharnvut, Kitjapat; Piyasakulkaew, Chaiwat; Kunakornsawat, Sombat (Asian Journal of Neurosurgery, 2025)
This is a retrospective cohort study.Full-endoscopic lumbar discectomy (FELD), a minimally invasive surgical procedure used to treat lumbar disc herniation (LDH), has been shown to be highly effective with fewer complications. This procedure can be performed using the interlaminar (IL) or transforaminal (TF) approach. The IL approach involves more anatomical structures than the TF approach. However, comprehensive data regarding preoperative and postoperative intervertebral disc height (IDH) changes for patients undergoing full-endoscopic discectomy through the IL versus the TF approach is yet to be documented.To compare the preoperative and postoperative IDH on radiographs in patients who underwent the FELD using the IL or TF approach.The medical records of patients diagnosed with LDH who underwent FELD between 2014 and 2022 were collected and analyzed. Pre- and postradiographic IDH and clinical scores, including visual analog scale-back pain (VAS-B), Oswestry disability index (ODI), and recurrent LDH, were assessed and compared over a follow-up period of at least 2 years.A total of 110 patients were included, 82 undergoing the IL procedure and 28 undergoing the TF procedure. The median IDH variance was consistent at 1.0 (interquartile range [IQR] 0.5, 2) for the IL and TF procedures, indicating no significant statistical variance. The IDH ratio was also comparable between the two groups, with the IL group at 84% and the TF group at 85%. However, a notable disparity was observed in postoperative IDH, with a median of 7.5 (IQR 6.5, 8.5) for the IL approach and 8.5 (IQR 7, 9.5) for the TF approach. Importantly, no statistical differences were found in clinical outcomes, including VAS-B, ODI, and recurrent LDH.After a 2-year follow-up for FELD, there is no significant difference in radiographic outcomes, IDH difference, and IDH ratio between the IL and TF approaches. Additionally, there is no apparent correlation between reductions in IDH and IDH ratio and the decrease in back pain scores (VAS-B) or ODI after the procedures.
Keywords: intervertebral disc height; lumbar disc herniation; radiographic; full-endoscopic lumbar discectomy; interlaminar; transforaminal